'My precious books and instruments': Jewish divorce strategies and self-fashioning in medieval Catalonia. Issue 5 (20th October 2017) - Roth, Pinchas
ABSTRACT: The divorce case between David Bonjorn and Esther Caravita, which took place in Girona and Perpignan in 1337, is extraordinarily well documented. Hebrew and Latin documents shed light on the stages of the controversy, the wide range of personalities involved in the case and, most notably, the strategies mobilised by the two sides in their attempt to uphold or invalidate the divorce. The ways in which personal strengths and weaknesses were utilised in this legal battle enrich recent scholarly discussions about legal strategy in medieval Europe.